Structural and Microvascular Changes in the Macular Are Associated With Severity of White Matter Lesions - Peng, Chenlei; Kwapong, William Robert; Xu, Shasha; Muse, Farah Mohamed; Yan, Jueyan; Qu, Man; Cao, Yungang; Miao, Hanpei; Zhen, Zhenxiang; Wu, Bo; Han, Zhao (Frontiers in Neurology, 2020)
Purpose: To characterize the microvascular and structural changes in the macular that occur in WMH using optical coherence tomographic angiography; we also aimed to explore the association between macular microvascular and structural changes with focal markers of brain tissue on MRI in WMH using the Fazekas scale. Methods: This study enrolled healthy participants who were stroke and dementia-free. MRI was used to image the cerebral white matter lesions and Fazekas scale was used to evaluate the severity of the white matter lesions. Optical coherence tomography angiography (OCT-A) was used to image the radial peripapillary capillaries (RPCs), macular capillary plexuses (superficial capillary plexus, SCP and deep capillary plexus, DCP) and thickness around the optic nerve head, peripapillary retinal nerve fiber layer (pRNFL). Results: 74 participants were enrolled and divided into 2 groups according to their Fazekas score (Fazekas score ≤1 and Fazekas score ≥2). Fazekas score ≥2 participants showed significantly reduced RPC density (P = 0.02) and DCP density (P = 0.012) when compared with Fazekas score ≤1 participants. Fazekas score ≥2 participants showed reduced pRNFL (P = 0.004) when compared to Fazekas score ≤1 participants. Fazekas scores were significantly associated with the pRNFL thickness (Rho = -0.389, P = 0.001), RPC density (Rho = -0.248, P = 0.035) and DCP density (Rho = -0.283, P = 0.015) respectively. Conclusions: Microvascular impairment and neuro-axonal damage are associated with the disease cascade in WMH. We have shown that RPC and DCP densities are significantly affected and these impairments are associated with the severity of the disease and cognitive function. OCT-A could be a useful tool in quantifying the retinal capillary densities in WMH.